2024
DOI: 10.7717/peerj.16740
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid metabolism by APOE4 in intrahepatic cholangiocarcinoma via the enhancement of ABCA1 membrane expression

Liqiang Qian,
Gang Wang,
Bin Li
et al.

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a malignancy with a dismal prognosis, thus the discovery of promising diagnostic markers and treatment targets is still required. In this study, 1,852 differentially expressed genes (DEGs) were identified in the GSE45001 dataset for weighted gene co-expression network analysis (WGCNA), and the turquoise module was confirmed as the key module. Next, the subnetworks of the 1,009 genes in the turquoise module analyzed by MCODE, MCC, and BottleNeck algorithms identified nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In 2011, Hanahan and Weinberg recognized the deregulation of cellular metabolism as a fundamental hallmark of cancer cells, characterized by disruptions in multiple bioenergetic pathways, including those for glucose, amino acids, and lipids [ 1 ]. Among these metabolic agents, lipids are multifunctional molecules that significantly influence various cellular processes, including the regulation of membrane glycoprotein function, control of membrane trafficking, apoptotic pathways, and drug transport [ 2 , 3 , 4 , 5 , 6 , 7 ]. In addition, research has shown that lipid metabolites can influence the surrounding microenvironment in ways that may promote tumor progression [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Hanahan and Weinberg recognized the deregulation of cellular metabolism as a fundamental hallmark of cancer cells, characterized by disruptions in multiple bioenergetic pathways, including those for glucose, amino acids, and lipids [ 1 ]. Among these metabolic agents, lipids are multifunctional molecules that significantly influence various cellular processes, including the regulation of membrane glycoprotein function, control of membrane trafficking, apoptotic pathways, and drug transport [ 2 , 3 , 4 , 5 , 6 , 7 ]. In addition, research has shown that lipid metabolites can influence the surrounding microenvironment in ways that may promote tumor progression [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%